Spontaneous coronary artery dissection masquerading as Takotsubo cardiomyopathy: a case report - Johnson, Shelsey W (Eur Heart J Case Rep, 2018)
BACKGROUND: Although obstructive coronary artery disease (CAD) is the most likely cause of acute coronary syndromes (ACS), nearly one in 20 individuals with clinical myocardial infarction (MI) do not have obstructive CAD. For many such individuals, presentation of Takotsubo cardiomyopathy frequently mimics presentation of MI, though spontaneous coronary artery dissection (SCAD) is an increasingly recognized aetiology of MI in women. CASE SUMMARY: This case report describes a woman with chest pain, found to have non-obstructive CAD on angiogram and left ventricular apical dysfunction on echocardiogram raising suspicion for Takotsubo cardiomyopathy. Additional suspicion for SCAD led to coronary CT angiogram (CCTA) which ultimately confirmed this diagnosis. DISCUSSION: Familiarity with a differential diagnosis for non-obstructive CAD is less common than that for obstructive coronary disease. This case emphasizes the clinical features that should raise suspicion for SCAD when Takotsubo is presumed and outlines the clinical utility of CCTA in making this diagnosis when angiography is unrevealing.